A beverage containing orange pomace improves laxation and modulates the microbiome in healthy adults: A randomised, blinded, controlled trial. (September 2019) - Dennis-Wall, Jennifer C.; Burns, Alyssa M.; Solch, Rebecca J.; Ukhanova, Maria; Dahl, Wendy J.; Christman, Mary C.; Boileau, Thomas; Brauchla, Mary; Shin, Jin-E; Nieves, Carmelo; Mai, Volker; Langkamp-Henken, Bobbi
Graphical abstract: Highlights: Healthy adults increased daily fibre intake by drinking orange juice with pomace. Stool frequency increased and stools were softer with pomace. When consumed daily, pomace provided physiological benefit. Bifidobacteria do not appear to mediate this benefit. Abstract: The aim was to assess whether citrus pomace increases stool frequency in healthy adults. In this randomised, blinded, controlled trial, healthy adults (62% females) received a beverage containing pomace (473 mL/day, providing 10 g fibre/day, n = 111) or control ( n = 110) for 3 weeks. Stool frequency, Bristol Stool Form Scale (BSFS), and Gastrointestinal Symptom Rating Scale (GSRS) scores were self-assessed. 24-h diet recalls were completed once/week. Stool microbiota were analysed by 16S rRNA sequencing and qPCR. Mean total daily fibre intake was higher with pomace vs. control ( P < 0.0001). Mean weekly stool frequency was higher, indicating improved laxation, with pomace vs. control ( P = 0.0281) and increased from baseline with pomace ( P = 0.0003) but was unchanged with control. Mean BSFS scores were higher with pomace vs. control ( P = 0.04). GSRS indigestion syndrome scores, specifically symptoms of gas and bloating, were higher with pomace, suggesting fermentation. Pomace intake increased faecal OTUs corresponding to Lachnospiraceae and Ruminococcaceae . Clinicaltrials.gov #NCT02979496 .